Risk factors influencing the outcomes in infants with epilepsy - Setyo Handryastuti; Irawan Mangunatmadja (Paediatrica Indonesiana, 2007)
Background Epilepsy in young children should always beconsidered as a symptom of an underlying brain disease. Parentsand caregivers often asked whether the seizures can be controlledand whether the epilepsy will affect the child development.Objective To find out risk factors influencing the outcomes ininfants with epilepsy.Methods This was a retrospective study on infants aged 1 monthuntil 12 months with recurrent epileptic seizures. We looked forthe risk factors as sex, types of medication, age at onset of seizure,epilepsy syndrome, etiology of epilepsy, history of neonatal seizure,first EEG features, and type of seizure for the last 6 month-period.The outcomes evaluated were controlled seizure and developmentalstatus.Results Hundred forty infants with epilepsy were reviewed,consisted of 84 (60%) infants with symptomatic epilepsy, and 56(40%) infants categorized as idiopathic. Forty-six (33%) infantshad controlled seizure, while 94 (67%) infants had uncontrolledseizure. Abnormal developmental status was found in 75 infants(54%). Abnormal developmental status was more found in infantswith polytherapy, age at onset of 1-4 months, symptomaticepilepsy, positive remote symptomatic, history of neonatal seizure,abnormality of first EEG, and uncontrolled seizure. Uncontrolledseizure of epilepsy was more found in infants with polytherapy,early age at onset (1-4 month old), symptomatic epilepsy, positiveremote symptomatic, history of neonatal seizure, and abnormalityof first EEG.Conclusion Our data indicate that classifying syndrome of epilepsythrough diagnostic screening and age of onset are important todetermine the outcomes.